New water mite species of the genus Albaxona Szalay, 1944 (Acari, Hydrachnidia, Aturidae) from Russia - Tuzovskij, Petr V. (Zootaxa, 2018)
Illustrated descriptions of four water mite species: Albaxona (Albaxona) primoryensis sp. n., A.(Albaxona) sidorovi sp. n., A. (Vietsaxona) similis sp. n., A. (Vietsaxona) steklyanukhaensis sp. n. from running waters of the Far East of Russia are given.